2023
DOI: 10.2903/sp.efsa.2023.en-8203
|View full text |Cite
|
Sign up to set email alerts
|

Communication of food‐related health risks and benefits – a systematic review (2018‐2022)

Abstract: In response to a request from the European Food Safety Authority (EFSA) to summarise the body of evidence in relation to communication of food‐related health risks and benefits ICF identified and reviewed the relevant scientific literature in six areas: (i) Consumer expectations about food production, food products and ingredients; (ii) Consumers’ preferred sources of information about food and food products; (iii) Consumer responses to risk benefit information about foods; (iv) Trade‐offs consumers make based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The review by Jaskiewicz et al. ( 2023 ) covered relevant papers on food‐related health risks and benefits from 2018 to 2022, while the report by Rodes‐Sanchez et al. ( 2024 ) completed data gaps with a focus on consumer trade‐offs related to risks and benefits.…”
Section: Risk–benefit Assessment Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…The review by Jaskiewicz et al. ( 2023 ) covered relevant papers on food‐related health risks and benefits from 2018 to 2022, while the report by Rodes‐Sanchez et al. ( 2024 ) completed data gaps with a focus on consumer trade‐offs related to risks and benefits.…”
Section: Risk–benefit Assessment Approachesmentioning
confidence: 99%
“…In a systematic review carried out for EFSA by Jaskiewicz et al. ( 2023 ), studies showed that consumer perceptions of food safety and health benefits vary widely and are shaped by several internal and external factors. For example, the perception of highly beneficial foods was found to rely more on individual personal beliefs and cultural background (e.g.…”
Section: Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a closer look shows that this is mostly the case for older generations, we can also find evidence that young people cite television as one of the top sources of food safety information (Tobin et al, 2005). In this context, preferences for food safety information sources differ by country and population group (Jaskiewicz et al, 2023). Nevertheless, mass media play an increasingly important role in informing people, and consumers often use them as information sources, sometimes even unknowingly (Valkenburg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%